Labour justice and alternative dispute resolution of collective and individual labour conflicts - Sappia, Jorge (ILO LimaPE, 2002)
Discusses the Declarations of Buenos Aires and Viña del Mar issued by the Inter-American Conference of Labour Ministers and their respective Plans of Action. Defines the tasks that the Ministers have set themselves in order to reach their proclaimed objectives.